The importance of nutritional care in an aging society - Nakayama, Naomi (World Nutrition Journal, 2024)
Japan has been facing serious aged society ahead of the world as seniors’ population has exceeded 27%. In this background, there are concepts of conventional life expectancy and healthy life expectancy. The period during which one can live independently without relying on nursing care is called healthy life expectancy and there is about ten years gap exists between these two life expectancies.